2016
DOI: 10.1111/jipb.12478
|View full text |Cite
|
Sign up to set email alerts
|

Wheat ear carbon assimilation and nitrogen remobilization contribute significantly to grain yield

Abstract: The role of wheat ears as a source of nitrogen (N) and carbon (C) in the grain filling process has barely been studied. To resolve this question, five wheat genotypes were labeled with 15 N-enriched nutrient solution. N remobilization and absorption were estimated via the nitrogen isotope composition of total organic matter and Rubisco. Gas exchange analyses showed that ear photosynthesis contributed substantially to grain filling in spite of the great loss of C due to respiration. Of the total kernel N, 64.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 53 publications
2
37
0
Order By: Relevance
“…In addition to flag leaf photosynthesis, ear photosynthesis also contributes to grain filling (Sanchez‐Bragado, Molero, Reynolds, & Araus, ; Zhou et al., ), especially under abiotic stress (Abbad, El Jaafari, Bort, & Araus, ). Moreover, the source–sink balance can regulate photosynthesis (Paul & Foyer, ) and grain filling (Paul, Oszvald, Jesus, Rajulu, & Griffiths, ), impacting directly on wheat yields (Valluru, Reynolds, & Lafarge, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to flag leaf photosynthesis, ear photosynthesis also contributes to grain filling (Sanchez‐Bragado, Molero, Reynolds, & Araus, ; Zhou et al., ), especially under abiotic stress (Abbad, El Jaafari, Bort, & Araus, ). Moreover, the source–sink balance can regulate photosynthesis (Paul & Foyer, ) and grain filling (Paul, Oszvald, Jesus, Rajulu, & Griffiths, ), impacting directly on wheat yields (Valluru, Reynolds, & Lafarge, ).…”
Section: Discussionmentioning
confidence: 99%
“…In cereals, although leaf photosynthesis plays a central role in biomass accumulation and yield formation over the entire growing season (Fischer et al, 1998;Gu et al, 2014), the photosynthetic activity of the ear has been shown to dramatically contribute to the pool of carbohydrates translocated to the developing grains over the post-anthesis stages (Tambussi et al, 2005;Tambussi et al, 2007;Maydup et al, 2010;Sanchez-Bragado et al, 2014). Although on an area basis, the ear CO 2 assimilation rate is lower than that of the flag leaf (Tambussi et al, 2005;Tambussi et al, 2007;Zhou et al, 2016), experimental evidence suggests that in bread and durum wheat, ear photosynthesis can contribute to the individual grain weight yield component by up to 70% in a large range of genotypes (Maydup et al, 2010) and contrasting environments (Sanchez-Bragado et al, 2014). Similarly to wheat, in Hordeum vulgare (barley), shading experiments revealed a significant contribution of the ear (up to 50%) to grain weight and therefore yield (Bort et al, 1994).…”
Section: Importance Of Photosynthesis In Non-foliar Cereal Organsmentioning
confidence: 99%
“…Furthermore, the assimilates produced in the spike are directly translocated into the grains (Carr and Wardlaw, ) leading to a contribution to GW between 10 and 45% depending on environmental conditions and genotype tested (Maydup et al , ; Sanchez‐Bragado et al , ). Indeed a large variation in gross spike A (calculated as the sum of A and dark respiration (R d ) as a proxy of respiration in the light) has been shown in both durum and bread wheat (Maydup et al , ; Molero et al , ; Zhou et al , ; Sanchez‐Bragado et al , ), suggesting the existence of natural genetic diversity for exploitation. For instance, the presence of awns (lemma‐derived organs) has been considered an important source of external CO 2 assimilation of the spike (Maydup et al , ) although other factors such a spike morphology (e.g.…”
Section: Exploiting Natural Variation In Photosynthetic Capacity and mentioning
confidence: 99%